Kegel’s Exercise could Reduce the Incidence of Postpartum Urinary Stress Incontinence - Nusratuddin Abdullah; Eddy Arsyad (Indonesian Socety of Obstetrics and Gynecology, 2014)
Objective: To investigate the cause of postpartum urin ary incontinence in primi gravida women and to determin e the relationship between stress urinary incontinence and kegel's exercise. Method: This was an observational study with cross sectional method , perform ed in instituti onal hospitals in Makassar. Thirty primigravida women who performed kegel's exercise were compared with 30 primi gravida women who did not perform kegel's exercise. Data were analyzed with independent-t sta tistical analysis. Result: Urinary incontinence were significantly lower in primigravida women who performed kegel's exercise (P=O.OOO). Conclusion: Kegel's exercise may reduce the incidence of postpartum stress urinary incontinence. Keywords: kegel's exercise, primigravida, urinary Incontinence.